Effect of Religiosity, Profit and Loss Sharing, Trust and Financing Intentions at Indonesian Islamic Bank (BSI) - Dewi Nurjannah; Heri Pratikto (Budapest International Research and Critics University, 2022)
Indonesia has a Muslim majority population and has a fairly large sharia banking business. The existence of the Indonesian Sharia Bank (BSI) creates competition between conventional bank managers to identify the strategy of the Indonesian Sharia Bank (BSI). The purpose of this study is to see how trust mediates religiosity, profit and loss sharing on MSME financing intentions. SPSS analysis and Sobel test were used in this study to see the role of mediation with a sample of 3 84 SMEs. The results of the study of religiosity have an influence on the beliefs and intentions of SMEs. Profit sharing Profit and Loss has an effect on trust but has no effect on MSME's intention to finance at BSI and Trust has a mediating role. In an effort to increase the factors that influence MSME's intention to finance, BSI Managers must create MSME trust, which provides the possibility for people of the Muslim faith to become financing customers.